Analisis Pengaturan Tata Tertib Penggunaan Jalan Raya Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Sakung Wibowo; Zainuddin Hasan; Nathaniel Benecia S; M Zacky Hasbana; Ariya Rama Cahya; M Imam Hasbana; Riski Adinata (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
The purpose of this research is to analyze the regulation regarding rules for the use of highways based on Law Number 22 of 2009 concerning Road Traffic and Transportation. The method used is normative and empirical juridical using primary and secondary data. Education on traffic rules is very important to be carried out and given to the next generation of the nation, starting from the level of kindergarten education to the senior secondary level. It is not only given to students but also must be equally understood by the general public at large. The application of socialization and explanation related to traffic rules is also very important to be held, it is hoped that students and also the general public can understand and comply with traffic rules properly. Community compliance in understanding these traffic signs can have a good impact so that the level of accidents and traffic decreases and does not endanger other road users.